Nanostructured high-performance dielectric block copolymers. Issue 83 (4th September 2015) - Liu, Wenmei; Liao, Xiaojuan; Li, Yawei; Zhao, Qiuhua; Xie, Meiran; Sun, Ruyi
Abstract : A dielectric block copolymer was synthesized by metathesis polymerization. It self-assembles into micelle or hollow sphere nanostructures, which exhibit excellent dielectric properties due to dipolar and interfacial polarization contributions. Abstract : A new type of insulating–conductive block copolymer was synthesized by metathesis polymerization. The copolymer can self-assemble into unique nanostructures of micelles or hollow spheres. It exhibits a high dielectric constant, low dielectric loss, and high stored/released energy density due to the strong dipolar and nano-interfacial polarization contributions.